2001
DOI: 10.1063/1.1381060
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between kinetics and thermodynamics of supercooled liquids

Abstract: We show that a single, reasonable assumption about the probability of rearrangements in a supercooled liquid necessarily implies a direct connection between kinetic and thermodynamic observables in these media. The prediction is tested against available experimental data for supercooled liquids spanning the range of observed kinetics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
32
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 21 publications
3
32
1
Order By: Relevance
“…For example, stronger substances tend to appear almost Arrhenius-like, tempting an interpretation using a simple activated event as the transport mechanism; fragile substances (like salol or TNB) exhibit a pronounced turnover in log τ (T ) that is not entirely satisfactorily fit by a single VTF law. Still, perhaps with an exception of polymeric melts [50], where detailed analyses pose some problems (to be discussed below), an unambiguous connection between the kinetics and thermodynamics of many glasses has been established in several recent works [42,43,44]. It seems beyond reasonable doubt that the decrease in the configurational, or excess liquid entropy with temperature is, at the least, qualitatively correlated with the observed concurrent rapid growth of the relaxation times, as supported by analyzing many substances.…”
Section: Fitting and Interpreting Experimental Relaxation Timesmentioning
confidence: 99%
“…For example, stronger substances tend to appear almost Arrhenius-like, tempting an interpretation using a simple activated event as the transport mechanism; fragile substances (like salol or TNB) exhibit a pronounced turnover in log τ (T ) that is not entirely satisfactorily fit by a single VTF law. Still, perhaps with an exception of polymeric melts [50], where detailed analyses pose some problems (to be discussed below), an unambiguous connection between the kinetics and thermodynamics of many glasses has been established in several recent works [42,43,44]. It seems beyond reasonable doubt that the decrease in the configurational, or excess liquid entropy with temperature is, at the least, qualitatively correlated with the observed concurrent rapid growth of the relaxation times, as supported by analyzing many substances.…”
Section: Fitting and Interpreting Experimental Relaxation Timesmentioning
confidence: 99%
“…Here, s* is the ''critical'' entropy of the rearranging region, ⌬ is the potential energy barrier per molecule, A has units of time and is weakly temperature dependent, and k B is the Boltzmann constant. This expression is a generalization of the Adam-Gibbs model that includes configurational and vibrational contributions to the entropy of the liquid (35).…”
Section: Cooperative Relaxation In Supercooled Liquids Elucidates Thementioning
confidence: 99%
“…other authors [18][19][20] and successfully verified for a large number of low molecular weight glass formers. 18 Equation (5) In this work, we have tested the validity of equation (5) for a large number of polymeric glass-formers.…”
mentioning
confidence: 99%
“…18 Equation (5) In this work, we have tested the validity of equation (5) for a large number of polymeric glass-formers. We have found that a correlation exists between dynamics fragility and thermodynamic properties for some polymers, whereas this correlation fails for others.…”
mentioning
confidence: 99%